Design of punch and die for trimming operation / Muhammad Asyraf Mohd Lizam - Mohd Lizam, Muhammad Asyraf (2022)
The versatility of the manufacturing sector necessitates the development of Special Purpose Machines in order to improve efficiency, lowering machining time and human workforce. After product been remove from the casting mould there are fins occurred at the product. To remove fins from castings, a specific function trimming machine can be used instead of traditional manual grinding in order to reduce machining time. This needs of punches and dies that are specialized to the workpiece.Using Solidwork 2021,the cad modelling of punch and die was created based on the selected design. The method of morphological table and pugh chart been using to select the best design. To make sure the design can be functioning, simulation of the design been conducted.